Swiss Сonfedеration experience on reception of migrants - N. A. Voronina (Управление)
The experience of Swiss Confederation in the field of integration of immigrants – one of the most economically developed countries of the world, occupying the leading position in Europe on the rate of foreign population in general demographic structure, – has been examined in the article. Evolution of the notions of “integration”, “social assimilation”, “acculturation” and others has been considered and different scientific approaches of Western researches to these notions have been adduced. Swiss immigration policy for the past decades has been traced and the modern integration policy of the country in the field of integration of foreign citizens into receiving society has been analyzed. A detailed analysis of the Swiss normative and legal framework in the field of migration, asylum and integration has been made also, and active development of migration laws over the last decade has been noted. Swiss migration politics, like in other developed Western countries-recipients of foreign labor, contains both: immigration policy (control over entry and stay of foreigners in the country) and policy of integration towards foreigners subject to integration processes.The process of integration of a foreign citizen into a new socio-economic, political and cultural environment is a complex, multidimensional phenomenon. There is a developed and scientifically grounded system of reception, accommodation and integration of foreigners and asylum seekers in Switzerland, which is based on constitutional values, respect and mutual tolerance. At the core of this system is a general strategy of integration, which constitutes a country’s core policy of integration and covers various areas: law, politics, labour issues, housing, education, culture and religion. In order to implement the policy of integration, in Switzerland there are being developed and implemented federal and cantonal integration programs. Integration processes management is administered through the developed system of state authorities at federal, cantonal and other levels, with active participation of different public organizations, including migrant organizations. Federal Council publishes reports on development of integration policy in the country, Federal Migration Office issues annual reports, numerous scientific researches on the theme are being conducted. At present each canton has its own Integration program, designed in accordance with the Modal cantonal program, that allows to implement different integration models, depending on regional requirements and priorities.